Development Of Netwatch Host Using Telegram As A Strengthening Model Of Institutional Performance Quality Governance - Wijaya, Alek; Kemala Jaya, Ade; Ayu Ningsih, Dinda; Lyanda, Doli (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Improving the quality of an institution's performance is very dependent on the facilities implemented in carrying out its work process. Currently, the facility being developed at the institution is by implementing IoT technology that utilizes various types of IoT devices. However, most institutions have not been able to monitor every IoT device used so that it also affects the quality of performance of the institution. Therefore, in the study, the Network Development Life Cycle (NDLC) method is used., researchers made efforts to strengthen the institutional performance quality governance model. The researchers developed Netwatch Host technology using Telegram, which is intended to monitor the condition of each IoT device in the institution and then send details of the condition via the Telegram Application. This is intended so that the IoT devices used by employees can be maintained so that they can respond quickly when there is an IoT device that is down or has a problem.